2014
DOI: 10.1103/physreva.89.053607
|View full text |Cite
|
Sign up to set email alerts
|

Geometric phase gate for entangling two Bose-Einstein condensates

Abstract: We propose a method of entangling two spinor Bose-Einstein condensates using a geometric phase gate. The scheme relies upon only the ac Stark shift and a common controllable optical mode coupled to the spins. Our scheme allows for the creation of an S z S z type interaction where S z is the total spin. The geometric phase gate can be executed in times of the order of 2π /G, where G is the magnitude of the Stark shift. In contrast to related schemes which relied on a fourth order interaction to produce entangle… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 53 publications
0
32
0
Order By: Relevance
“…This formulation could be generalized to other systems, such as quantum dots placed in a microcavity [16]. Another application is to atomic BEC systems, where an ac Stark shift is readily realized via coupling of cavities to optical transitions of atoms [36].…”
Section: Discussionmentioning
confidence: 99%
“…This formulation could be generalized to other systems, such as quantum dots placed in a microcavity [16]. Another application is to atomic BEC systems, where an ac Stark shift is readily realized via coupling of cavities to optical transitions of atoms [36].…”
Section: Discussionmentioning
confidence: 99%
“…Comparing this to (38), we observe that the difference is that the second BEC's labels must be changed to k → N − k. This can be achieved using the transformation e iS z π/2 |k (x)…”
Section: Two-axis Two-spin Epr Statementioning
confidence: 96%
“…[33,34] where it was found that a complex structure of entanglement is present, with a time dependence showing fractal characteristics. Methods to generate this state have been examined in numerous works [33][34][35][36][37][38][39]. Procedures to generate other types of entangled states have also been studied [40,41].…”
Section: Introductionmentioning
confidence: 99%
“…Several proposals for such an interaction exist, including photon mediated cavity based methods [27,28,30] and interactions with state-dependent forces [45]. The type of entanglement that is produced by such an interaction has an exotic structure with fractal properties (the "devil's crevasse") [34,46].…”
Section: Example Applicationsmentioning
confidence: 99%
“…In particular, the ability of realizing BECs on atom chips allows for the possibility of excellent coherent control [25], and performing tasks such as spin squeezing [26]. This allows for a naturally scalable architecture where multiple BECs could be produced on the same chip, allowing for the possibility of entanglement between BECs [27][28][29][30]. While entanglement between two BEC has not been realized to date, entanglement between a BEC and an atom has been demonstrated [31].…”
Section: Introductionmentioning
confidence: 99%